Gastrointestinal Symptoms and Dopamine Transporter Asymmetry in Early Parkinson's Disease - Murtomäki Kirsi; Mertsalmi Tuomas; Jaakkola Elina; Mäkinen Elina; Levo Reeta; Nojonen Tanja; Eklund Mikael; Nuuttila Simo; Lindholm Kari; Pekkonen Eero; Joutsa Juho; Noponen Tommi; et al. (WILEY, 2022)
Background: The neurophysiological correlates of gastrointestinal symptoms (GISs) in Parkinson's disease (PD) are not well understood. It has been proposed that in patients with a gastrointestinal origin of PD dopaminergic neurodegeneration would be more symmetric.
Objectives: The aim is to assess the associations between GISs and asymmetry of nigrostriatal dopaminergic neurodegeneration in PD.
Methods: Ninety PD patients were assessed using motor and GIS scales and 123 I-FP-CIT SPECT. We calculated the asymmetry index and the predominant side of motor symptoms and dopamine transporter (DAT) imaging defect and assessed their association with GISs.
Results: There were no significant differences in GISs between symmetric and asymmetric dopaminergic defect. Left predominant defect was related to more GIS and higher constipation scores.
Conclusions: GISs were associated with left predominant reduction in putaminal DAT binding but not asymmetry per se. It remains open whether left-sided DAT deficit is related to more pronounced GI involvement or symptom perception in PD. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson Movement Disorder Society.